Manajeman Proyek Sistem Informasi Barbershop Rama Berbasis Web Dengan Menggunakan Metode Waterfall - Putri, Suci Syah; Yahfizam, Yahfizam (Lembaga Riset Mutiara Akbar, 2024)
This research discusses the implementation of the Barbershop Rama Web-Based Information System, focusing on improving operational efficiency and customer experience in the personal care industry. The Waterfall Method is employed as a structured development approach, involving stages such as needs analysis, design, implementation, testing, and maintenance. The implementation results are depicted in use case, activity, and database relation diagrams. The system facilitates customer, service, and appointment management. The web design follows the Laravel framework. The research conclusion includes contributions to software development literature and the potential application of information technology in the personal care industry.